2018
DOI: 10.1186/s12911-017-0580-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 7-day, 30-day and 60-day all-cause unplanned readmission: a case study of a Sydney hospital

Abstract: BackgroundThe identification of patients at high risk of unplanned readmission is an important component of discharge planning strategies aimed at preventing unwanted returns to hospital. The aim of this study was to investigate the factors associated with unplanned readmission in a Sydney hospital. We developed and compared validated readmission risk scores using routinely collected hospital data to predict 7-day, 30-day and 60-day all-cause unplanned readmission.MethodsA combination of gradient boosted tree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 34 publications
4
75
2
1
Order By: Relevance
“…While growing research [ 1 7 ] supports that 7-day readmissions are more preventable than 30-day readmissions, 30-day readmissions continue to dominate the readmission prediction space. Few studies explicitly have developed prediction models for 7-day readmissions [ 8 , 12 ]. Herein, we provide empirical evidence that a previously validated, multi-condition 30-day EHR-based readmission risk prediction model can also be used to predict 7-day readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While growing research [ 1 7 ] supports that 7-day readmissions are more preventable than 30-day readmissions, 30-day readmissions continue to dominate the readmission prediction space. Few studies explicitly have developed prediction models for 7-day readmissions [ 8 , 12 ]. Herein, we provide empirical evidence that a previously validated, multi-condition 30-day EHR-based readmission risk prediction model can also be used to predict 7-day readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…However, current risk prediction models often only identify patients at risk for 30-day readmission [ 8 10 ] and often fail to use electronic health record (EHR) data effectively to allow for real-time operationalization of the model [ 10 , 11 ]. There is a paucity of research developing prediction models for adult 7-day readmissions [ 8 , 12 ], which may be due to federal financial penalties tied to 30-day readmissions. Yet, to our knowledge, no study has investigated if a 30-day model can be reapplied effectively to predict the important subset of 7-day readmissions.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the overall 30-day readmission rate was higher than that reported in previous studies. 21,22 This could be because, unlike other studies 8,22 that included patients admitted under all specialties, we included only unplanned index medical admissions, which are generally more complicated admissions with a high risk of readmission. 23 Relative to the number of readmissions to the index hospital, the proportion of patients readmitted to a different hospital was less than reported in other studies, 9,12 and presumably local factors have some relevance in the size of this proportion.…”
Section: Discussionmentioning
confidence: 99%
“…23,27 Recent works described its potential in the medical field. [26][27][28][29][30][31][32][33] Analysis Continuous features are reported as the median with the spread reported as interquartile range (IQR). Categorical elements are reported as percentages.…”
Section: Machine Learning Modelmentioning
confidence: 99%